Napravlennost' i puti formirovaniya motivov sportivnoi deyatel'nosti v kollektivakh sbornykh komand Rossii - Sysoev, Yu. V. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
In this article author analyzes the problems of motivational sphere of elite athletes. On the basis of the analysis he suggests to construct so called situative model of sport activities. This model should consist of many different psychological situations, problems, circumstances which will teach athletes to conduct themselves in any cases of sport life. The author applies "atomization in sport in his researches to explore a counteraction to collective relationships by propaganda and fosterage of an extra-individualism, selfishness and personal alienation from collective. The model, by the author opinion, will be very effective in process of athletes preparing to important sports events, such as European Championships and Olympic Games.